Wdrażanie i organizacja controllingu w przedsiębiorstwach produkcyjnych. Analiza wyników badań - Janczyk-Strzała, Elżbieta (Implementation and Organisation of Responsibility Areas in Production Companies, 2006)
This article is dedicated to the significant role of controllership in contemporary production companies. It describes the process of its implementation. Presented conclusions are based on the conducted research.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1139, s. 120-143